PEMETAAN LUBANG BEKAS TAMBANG (MINE VOID) MENGGUNAKAN DATA CITRA SATELIT SENTINEL-2 - Lestari, Leta
The open pit mining method is the most widely mining method used in Indonesian coal mines. At the end of an open pit mining activities, it has the potential to leave voids, which are caused by a shortage of overburden during the backfilling process. The voids left have the potential to be filled with rainwater and groundwater and form a pit lake. In post-mining planning, pit lakes are categorized as “Reklamasi Bentuk Lain” that can be used as water reservoirs, flood control, ecosystem buffering, aquaculture, agriculture and/or power generation. However, if it is left without a proper management, the void (which will become a pit lake) has the potential to cause negative impacts on the community and the surrounding environment. Therefore, the presence of voids that are formed needs to be identified spatially so that they can be monitored as early as possible and management options can be arranged earlier.